Graph-based modeling of hybrid-electric aircraft electro-thermal system - Choong, Hui Qian (Nanyang Technological University, 2021)
Technological advancements in power generation have led to the concept of electrification in aircraft. Electrification optimizes the power flow between multi-physical domains for better aircraft performance and efficiency. Yet, power flow analysis of multi-physics system is complex, due to the need to interconnect components of various physical domains. To reduce system design complexity, a model-based design must be able to determine the dynamic states of the multi-physics interaction, provide accurate state estimations, and evaluate the system behaviour of all the energy domain. This report studies the use of graph-based modeling methodology to simplify the complexity of designing a multi-physical system, in addition to its capability to evaluate the dynamic states of the physical domains during system-to-system interactions. The formulation of graph-based models of aircraft electrical and thermal components based on the principle of conservation of energy is defined and integrated into a dynamic system. Electrical and thermal management systems are evaluated using graph-based models in MATLAB/Simulink with Aerospace Power System Toolbox (APST). Finally, a candidate graph-based model of a Hybrid-Electric (HE) aircraft electro-thermal system simulation is studied, highlighting the suitability of graph-based models for complex multi-physics systems.